Study of Organic Pollutants in the Muscles of fish Collected from El-Mahmodia Stream at El-Beheira Governorate, Egypt - E H Radwan; EL-Hassan M Mokhamer; K H Radwan; M Elsaka (International Journal of Aquaculture Research and Development, 2019)
The purpose of this study is to evaluate the impact of organic pollution of EL-Mahmodia canal on the fish (Oreochromis niloticus)muscles tissues collected from two sites at EL-Mahmodia canal in summer and winter 2017. EL-Mahmodia canal is exposed to excessive of effluents which impact fish. The present results showed high concentrations of organic pollutants, particularly in winter. Organic pollutants were analyzed using the gas-chromatography-mass spectrometry (GC-MS). A variety of environmental screening studies concerning varieties of water pollutants in Egypt, the target of the present study was to scan the organic pollutants of El-Mahmodia stream at El-Beheira Governorate, Egypt within the muscles of Tilapia fish. Within the present study, it was found that; the analysis of fish muscles in summer season showed a high level of organic pollutants. The organic pollutants that are reported in the muscle of fish in the polluted site were reported as; Dimethomorph-(E), Hexestrol, Diisobutyl phthalate, Diamyl phthalate, Di-n-propyl phthalate, Chlorpyrifos, Phorate sulfoxide, Exaltolide (15-Pentadecanolide), Chlorfenapyr, Pyridate, Ethofumesate, Bis (2-ethylhexyl)phthalate, Dicyclohexyl phthalate, Di-n-octyl phthalate, Tricresylphosphate, meta-, XMC (3, 4-Dimethylphenyl N-methyl, XMC (3,5-Dimethylphenyl N-methyl, Hexestrol, Thymol, Kinoprene, Diisobutyl phthalate, Diisobutyl phthalate, Di-n-hexyl phthalate, Di-n-hexyl phthalate, Carbofuran-3-keto, Tefluthrin, cis-, Carbofuran-7-phenol, Carbofuran, Dicyclohexyl phthalate, Di-n-propyl phthalate, Di-n-propyl phthalate, Bis(2-ethylhexyl)phthalate, Ethofumesate, Hexestrol, Kinoprene, Di-n-hexyl phthalate, Exaltolide (15-Pentadecanolide), Spiroxamine metabolite (4-tert-b), Chlorfenapyr, Tricresylphosphate, para, Tricresylphosphate, meta-, Tricresylphosphate, ortho-, XMC (3, 5-Dimethylphenyl N-methyl, XMC (3,4-Dimethylphenyl N-methyl, Fluroxypyr-1-methylheptyl ester, Cashmeran, Propargite metabolite (Cyclohexa), and Quinoclamine. The present results showed that Diisobutyl phthalate, Bis(2-ethylhexyl)phthalate, Pyridate and Ethofumesate were detected in winter season in the polluted site, whereas, Bis (2-ethylhexyl) phthalate, and Pyridate were the only organic pollutants that were found in winter in the reference site. The accumulation patterns of organic pollutants percentage in the polluted site in summer in the muscles of O. niloticus were in the following order: Chlorpyrifos> Diamyl phthalate> Diisobutylphthalate> Di-n-butylphthalate> Diamyl phthalate> Bis (2-ethylhexyl) phthalate, whereas, in the reference site in summer, it was Chlorpyrifos> Chlorfenapyr> Di-n-butylphthalate> Diisobutylphthalate> Hexestrol> Di-nhexyl phthalate. The accumulation patterns of organic pollutants in the polluted site in winter in the muscles of O. niloticus, were in the following order: Bis(2-ethylhexyl)phthalate> Pyridate> Ethofumesate, whereas in the reference site it was; Bis (2-ethylhexyl)phthalate> Pyridate.
Keywords: pollution